Simultaneus bilateral spontaneus pneumothoraces - Şimşek, Fatma; Akçıl, Murat; Balkanay, Ozan; Demirkaya, Ahmet; Kaynak, Kamil (Cerrahpaşa Medical Journal, 2014)
Pneumothorax can be briefly described as the entrance of air into the pleural cavity. Under normal conditions, there is 5-10 ml liquid material, but no air between the visceral and parietal pleura. Pneumothorax is one of the most frequent thoracic surgery emergencies. Spontaneous pneumothorax usually occurs in slim and tall young male persons and has to be operated urgently. It is divided into two groups: primary and secondary. It is rarely seen bilaterally. Its treatment varies from urgent surgical operation to mere inspection. As it is a rarely seen phenomenon, we have discussed a 21 years old male patient with bilaterally concomitant spontaneous pneumothorax in the light of related literature.